Representasi Hubungan Percintaan pada Lirik Lagu JKT48 - Putri Ariyani, Destria; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2019)
JKT48 often tells about love stories from the perspective of women, and it shows that love is a main theme which considered as important for women. Romantic relationship stories then become a theme which often found in women singers’ song lyrics, and it shows its importance for women. Thus, this research aims to find out how romantic relationship itself is represented in JKT48’s song lyrics. This research used constructivism paradigm with qualitative approach and semiotic as its analysis method. The data collection techniques use the study of documents and the study of bibliography. The data analysis technique used Barthes’s narration codes or Barthes lexia codes which consisted of hermeneutics code, semic code, symbolic code, proairectic code, and cultural code. The result of this research showed that: there is a liking toward the other person in the form of physical and non-physical attraction, physical beauty was perceived as beneficial for women to achieve the ideal romantic relationship, keeping the virginity is perceived as a principle, men prefer a physical beauty as a criterion for their romantic relationship partner, women can reject romantic relationship if they haven’t fulfill their own idealism on the relationship itself, and there was an integration of meaning and hope in the events.